Effects of pH and temperature on glucose production from tapioca starch using enzymatic hydrolysis : a statistical approach - Siti Nor Shadila, Alias (2009)
The aim of this study was to maximize the glucose concentration produced from enzymatic hydrolysis of tapioca starch. The tapioca starch was enzymatically hydrolyzed using α-amylase from Bacillus lichenformis followed by amyloglucosidase action from Aspergillus niger. Effects of liquefaction temperature (X1), saccharification temperature (X2), liquefaction pH (X3) and saccharification pH (X4¬) were evaluated. 24 full factorial design with 1 replicate and 3 centered point was applied to determine the significant parameters affecting the production of glucose concentration. The range of the factors employed were 60 -90˚C (liquefaction temperature), 40-60˚C (saccharification temperature), 5-7 (liquefaction pH) and 4-6 (saccharification pH). The maximum glucose concentration obtained experimentally was 329.10 g/L. The ANOVA shows that the effects of liquefaction temperature and saccharification pH on glucose production were very significant. The saccharification temperature and liquefaction pH, on the other hand did not influence the glucose production. The optimum liquefaction temperature, saccharification temperature, liquefaction pH and saccharification pH suggested by the design of experiment were 90˚C, 60˚C, 7 and 6 respectively. From that optimum condition, the maximum glucose concentration of 331.8 g/L was estimated.